Crisis of governability in Guyana - Ryan, Selwyn (2003)
Looks historically at the political, social and economic situation in Guyana. Examines the social, economic and political conflict which has left many of its citizens with feelings of hopelessness and despair. Notes that at the economic level, economic growth which was visibly in evidence following the change of regime in 1992, has come to a near halt. Opines that at the social level stress is reflected in the deep concerns and anxieties about unofficial and official crime.